2021
DOI: 10.14719/pst.1357
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into plant growth promoting genes inherent in bacterial endophytes of Emilia sonchifolia (Linn.) DC

Abstract: Studies on the genome of endophytes reveal the metabolic potential of endophytic microbiome including both culturable and unculturable fractions. The metagenome analysis through the Illumina HiSeq platform gives access to the genetic data encrypted for the molecular machinery, which takes part in plant growth promotion activity of the endophyte in various aspects including production of plant growth hormones and enhancing nutrient availability for the host plant. The present work was undertaken to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Multiple metagenomic analyses have been carried out for investigating the genes related to plant growth-promoting traits of bacterial community from soil samples of oil field at Wietze ( Eze et al, 2021 ), from maize rhizosphere in the South Africa ( Molefe et al, 2021 ), associated with the root of sugar beet ( Tsurumaru et al, 2015 ), and the endophytes of Emilia sonchifolia (Linn.) DC ( Urumbil and Anilkumar 2021 ). These metagenomic analyses showed structural and functional diversity of plant microbiomes and allowed identification of genes and taxa putatively related to plant growth promotion.…”
Section: Omics Methods For Assaying Molecular Mechanisms Of Pgpbmentioning
confidence: 99%
“…Multiple metagenomic analyses have been carried out for investigating the genes related to plant growth-promoting traits of bacterial community from soil samples of oil field at Wietze ( Eze et al, 2021 ), from maize rhizosphere in the South Africa ( Molefe et al, 2021 ), associated with the root of sugar beet ( Tsurumaru et al, 2015 ), and the endophytes of Emilia sonchifolia (Linn.) DC ( Urumbil and Anilkumar 2021 ). These metagenomic analyses showed structural and functional diversity of plant microbiomes and allowed identification of genes and taxa putatively related to plant growth promotion.…”
Section: Omics Methods For Assaying Molecular Mechanisms Of Pgpbmentioning
confidence: 99%
“…The process is described in a study which identified specific genes involved in plant growth promotion in the endophytic bacteria of the medicinal plant Emilia sonchifolia (Linn.) [ 96 ], which pave the pathway for future genome editing.…”
Section: Future Opportunities and Research Directionsmentioning
confidence: 99%